Socio-economic Study of Small Farmers of Jammu and Kashmir - Parveen Kumar; M. S. Nain (Indian Journal of Extension Education, 2013)
The present study was conducted in Jammu and Kathua districts of Jammu and Kashmir. From each district, three villages were selected randomly. Thus, a total of six villages were selected. A study was carried out prior to the research study to know about the major crops grown for food grains, livestock and the availability of water for irrigation. Wheat and paddy constitute the major crops grown in these villages. Potato is also cultivated by limited number of families. Barseem is grown for live - stock and mustard is also grown by some respondents. Almost the entire area is irrigated. From each selected village fifteen respondents were selected purposively. The selection of respondents was on the basis of their size of land holdings. Farmers having land holdings up to 2 hectares were selected. The final sample, thus consisted of 90 respondents. Data was obtained by a well prepared semi-structured interview schedule, which also consisted of a set of eight statements related to non adoption of technology. The huge yield gap between the yields obtained and the maximum obtainable yields have to be narrowed. There is a considerable potential to increase production and yield per hectare by the introduction of new inputs and improved practices of cultivation.